Don't be undersold! - STEENKAMP, Jan-Benedict E.M. (Institutional Knowledge at Singapore Management University, 2009)
"Aldi" is a word that strikes fear in the hearts of brand managers across Europe. A chain of low-budget retail stores with sales of $73.5 billion in 2008, Aldi invented what is commonly referred to as the hard-discount store, a format that is destroying between a quarter and a half trillion dollars in brand sales annually.Brand executives at major consumer packaged goods companies have mostly been caught off guard by this success, The authors' research identified four key misconceptions that explain why: (1) Hard discounters can succeed only in Europe; (2) they attract only the poor; (3) they offer inferior quality; (4) their success is a recessionary phenomenon.Aldi, Lidl, and other hard discounters keep costs low in part by restricting as much as 90% of their stock to their own private labels. But, as they are beginning to realize, that practice can gain only so much market share. A judicious mix of store labels and manufacturers' brands will win new customers for both. And brand manufacturers that fear sales cannibalization can take several proactive steps: sell unfamiliar sizes at the discounters, offer brands with a small market share, carefully manage the price gap, make shipping boxes attractive, and keep their brands dynamic.